Pharmacoeconomic evaluation of aspirin therapy in pharmaceutical prevention of the first acute myocardial infarction in patients with stable angina - A. Yu. Kulikov; A. V. Kontsevaya (Кардиоваскулярная терапия и профилактика)
Aim. To perform pharmacoeconomic analysis of the standard therapy vs. standard therapy plus enteric-coated aspirin, Aspirin Cardio®, in preventing acute myocardial infarction (AMI) among patients with stable angina (SA). Material and methods. To assess the effectiveness of Aspirin Cardio®, the results of the randomised SAPAT Study were used. The costs of treating 100 SA patients for 50 months were modelled for standard therapy only and compared with the study results for standard therapy plus Aspirin Cardio®. Two types of analysis were performed: “budget impact analysis of in- and outpatient treatment of SA” and “cost-effectiveness” analysis. Results. Overall costs of treating 100 SA patients for 50 months were 7 826190 roubles for standard therapy with betaadrenoblockers, and 7 751072 roubles – for standard therapy plus Aspirin Cardio®. Therefore, costs were lower by 75118 roubles per 100 patients treated with standard therapy and Aspirin Cardio® for 50 months. Costs of preventing one AMI case were lower for combined therapy than for standard therapy alone: 81248 vs. 84699 roubles, respectively. Total costs of preventing one AMI case are lower by 34144 roubles for combined therapy, comparing to standard therapy only. The combination of standard therapy and Aspirin Cardio® reduces mortality in many SA patients, due to decreased sudden death rates, and also cuts costs on preventing one death by 62598 roubles. Conclusion. Pharmacoeconomic analysis demonstrated that a combination of standard therapy plus Aspirin Cardio® improves “cost-effectivenes” ratio in SA patients.